Simultaneous approach for patients with synchronous colon and rectal liver metastases: Impact of site of primary on postoperative and oncological outcomes. Issue 4 (April 2021) - Conci, Simone; Ruzzenente, Andrea; Pedrazzani, Corrado; Isa, Giulia; Turri, Giulia; Campagnaro, Tommaso; Valdegamberi, Alessandro; Bagante, Fabio; Marchitelli, Ivan; Guglielmi, Alfredo
Abstract: Background and aims: We aimed to investigate the impact of the site of the primary on postoperative and oncological outcomes in patients undergone simultaneous approach for colon (CC) and rectal cancer (RC) with synchronous liver metastases (SCRLM). Patients and methods: Of the 220 patients with SCRLM operated on between Mar 2006 and Dec 2017, 169 patients (76.8%) were treated by a simultaneous approach and were included in the study. Two groups were considered according to the location of primary tumor RC-Group (n = 47) and CC-group (n = 122). Results: Multiple liver metastases were observed in 70.2% in RC-Group and 77.0% in CC-Group (p = 0.233), whilst median Tumor Burden Score (TBS) was 4.7 in RC-Group and 5.4 CC-Group (p = 0.276). Severe morbidity (p = 0.315) and mortality at 90 days (p = 0.520) were comparable between RC-Group and CC-Group. The 5-year overall survival (OS) rate was similar comparing RC-Group and CC-Group (48.2% vs. 45.3%; p = 0.709), but it was significantly different when considering left-CC, right-CC and RC separately (54.5% vs. 35.2% vs. 48.2%; p = 0.041). Primary tumor location (right-CC, p = 0.001; RC, p = 0.002), microscopic residual (R1) disease at the primary (p < 0.001), TBS ≥6 (p = 0.012), bilobar metastases (p = 0.004), and chemotherapy strategy (preoperative ChT, p = 0.253; postoperative ChT, p = 0.012; and perioperative ChT, p < 0.001) resulted to be independent prognostic factors at multivariable analysis. Conclusion: In patients with SCRLM, simultaneous resection of the primary tumor and liver metastases seems feasible and safe and allows satisfactory oncological outcomes both in CC and RC. Right-CC shows a worse prognosis when compared to left-CC and RC.